Hypospadic Cripple: How To Avoid - Bisono, Bisono (Jurnal Plastik Rekonstruksi, 2012)
The term hypospadic cripple is very apt to use for hypospadic patient who has underwent several unsuccessful reconstruction attempt. The meaning of the word cripple is uncapable to function properly. If it is used for condition after failure of several attempt of reconstructions in hypospadia repair, the meaning of severe damage should apply; a crippled penis with fistula, stricture, contracture and less healthy skin cover.